PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENS (TGT) PADA PEMBELAJARAN MATEMATIKA MATERI PELUANG DI SMP NEGERI 6 TONDANO - Wenas, John R; Pesik, Anekke; Apelia, Giovanni Aditia (JSME (Jurnal Sains, Matematika & Edukasi), 2020)
ABSTRACT. The purpose of this research was to determiner the effect of the TGT type of cooperative learning model of the students learning outcomes on the probability lesson. This research categorized as quasi-experimental. The research was conducted at SMP Negeri 6 Tondano during the odd semester of the 2019/2020 academic year. The subject of this research were students of class VIII A and VIII B, with 15 students in each class. Data collection in this research used test, which was given after the treatment in the experimental and the kontrol classes. Data analysis used an average t-test comparing two different groups. The result of the data analysis showed that the average of the students learning outcomes in the experimental class was 74,667. The result of the hypothesis test obtained tcount=2.646 and ttable=1.75, tcount>ttable, so H0 is rejected, thus it can be concluded that the average student learning outcomes used TGT cooperative type learning model were higher than the average of the student learning outcomes used the conventional learning model on probability lesson. Key Words: Conventional, Probability, TGT